COMPARISON AS A WAY TO CREATE A COMIC IMAGE OF A POLITICIAN IN THE AMERICAN MEDIA (BASED ON THE MATERIAL OF THE AMERICAN NEWS ARTICLES) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-2-41-49The relevance of the article is due, on the one hand, to the interest of linguists in the study of linguistic means and techniques of creating the comic in the media discourse, and, on the other, to the insufficient knowledge of comparison as a way of creating comic images of politicians. The paper identifies the types of comparative constructions involved in the creation of negative images of American politicians, classifies the objects of comparison and identifies the reasons for choosing these objects, which serve as a way of accentuating the negative characteristics of politicians.Key words: comic, comparison, object of comparison, image of a politician, critical discourse analysis, political modalization